Hubungan Pola Komunikasi Orang Tua Terhadap Perkembangan Sosial Anak di TK Alam Surya Mentari Surakarta Tahun Ajaran 2015/2016 - Latifah, Choirunnisa Nurul; , Ilham Sunaryo, M.Pd.AUD (2016)
The quality of relation and communication that are given by parents to children will determine the quality of childern's social development. A fully of intimate relationship and two ways communication between children and parents are the key of determining children's social development. A communication which must be done is integrative communication, where a father, a mother, and children mixed up with comfortable conversation and avoid model of comunication which is dominative or be willing dominant in conversation. Communication pattern which is built will influence psychological development and children's thought, and it influences children's psychological condition directly and indirectly. A family has a function optimally if there is an open communication pattern, there is an attitude for accepting, supproting, feeling safety and comfortable and having spritual life in harmony. The objective of the study is to know the relation of parents's communication pattern to children's social development in TK Alam Surya Mentari academic year 2015/2016. The type of the study was descriptive correlational research. This research was done in TK Alam Surya Mentari academic year 2015/2016 adressed on Jl. Siwalan No. 45 Jajar Laweyan Surakarta. The population of the study were 129 children of TK Alam Surya Mentari with percentage of error 1% in Kracjie table, then the sample which could be used was 92 students. The technique of sampling used random sampling. The technique of analyzing data is a correlation Product Momen. The result of the study was that there was a relation between interactional of parents' communication pattern to children's social development in TK Alam Surya Mentari academic year 2015/2016. It could be evidenced by the result of r pearson correlation 0,781. Thus all significance 1% although 5% rxy > rtabel = 0,781 > 0,267 > 0,207 meant that Ho is refused and Ha was be accepted which means that there is a relation between interactional of parents' communication pattern and children's social development in TK Alam Surya Mentari Surakarta 2015/2016 academic year.